Prinsip Utmost Good Faith Dalam Perjanjian Asuransi Kerugian - Santri, Selvi Harvia (UIR Law Review, 2017)
Insurance as a business activity are required to meet the principles of insurance law. One of the principles that must be adhered to is the principle of utmost good faith. This principle states that an insured is required to provide truthful information about what the insured to the insurer. By law, this principle is set in the Code of Commerce. The lack of honesty in the insurance business will have an impact on the cancellation of appointments per disability insurance because there is an element of the will. In accordance with Article 251 Commercial code which reads "Any information that is false or incorrect, or each do not tell things that are known by sitertanggung, however good faith to him, such a character, so if sipenanggung have to know the real situation, the agreement would not be covered by the same terms, resulting in the cancellation of pertangungan